2015
DOI: 10.5812/hepatmon.23564
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Prolonged Treatment With Pegylated Interferon (Peg-IFN) and Ribavirin in Thalassemic Patients With Hepatitis C Who Relapsed After Previous Peg-IFN-Based Therapy

Abstract: Background:Most thalassemic patients with chronic hepatitis C virus (HCV) infection do not respond to therapy with pegylated interferon (Peg-IFN) plus ribavirin (RBV) due to hepatic siderosis and RBV dose reduction caused by RBV-induced anemia.Objectives:In the present study, we recruited HCV genotype 1-infected thalassemic patients who had relapsed after a 48-week treatment with Peg-IFN plus RBV in order to evaluate the efficacy of a 72-week regimen of Peg-IFN plus RBV.Patients and Methods:In this retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Based on these findings, experts and guidelines recommended to intensify the treatment by adding RBV or prolongation of treatment to a 24-week course when patient harbor cirrhosis and/or previous history of treatment and/or NS5A RASs (20). The on-treatment response was the most important predictor of response of SVR in the IFN-based regimens; however, with the introduction of highly efficient IFN-free DAA regimens, the importance of on-treatment response faded (21)(22)(23)). In the current study, the only case with viremia at the week 4 of treatment achieved SVR; however, large-scale studies are needed to clarify the importance of on-treatment response in clinical decision-making in the IFN-free regimens era.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, experts and guidelines recommended to intensify the treatment by adding RBV or prolongation of treatment to a 24-week course when patient harbor cirrhosis and/or previous history of treatment and/or NS5A RASs (20). The on-treatment response was the most important predictor of response of SVR in the IFN-based regimens; however, with the introduction of highly efficient IFN-free DAA regimens, the importance of on-treatment response faded (21)(22)(23)). In the current study, the only case with viremia at the week 4 of treatment achieved SVR; however, large-scale studies are needed to clarify the importance of on-treatment response in clinical decision-making in the IFN-free regimens era.…”
Section: Discussionmentioning
confidence: 99%
“…This will lead to the resistance of those carrying the ITPA variant to anemia and severe hemoglobin decrease following RBV‐related treatments . Ribavirin is known as a purine nucleoside analogue and one of the fundamental treatments of chronic hepatitis C . The ITPase activity may lead to anemia induction via endogenous purines .…”
Section: Introductionmentioning
confidence: 99%
“…The extension of PEG IFN/RBV dual therapy was also attempted in another situation. A recent study reported that thalassemic patients with HCV infection, who did not respond to dual therapy due to hepatic siderosis and anemia, benefited from an extension of regimen . The strategy of extending dual therapy with PEG IFN/RBV would be applicable for SMV triple therapy.…”
Section: Discussionmentioning
confidence: 99%